IMPLEMENTAS1 KEBIJAKAN UNDANG-UNDANG NOMOR 23 TAHUN 2006 TENTANG ADMINISTRASI KEPENDUDUKANTERHADAP PARTISIPASI MASYARAKAT UNTUK MENGURUS AKTA KELAHIRANDI KABUPATEN TAPANULI SELATAN - SABRIN . (JURNAL ILMIAH KOHESI, 2018)
The Unitary State of the Republic of Indonesia based on Pancasila and the 1945 Constitution of the Republic of Indonesia are essentially obliged to provide protectionand acknowledgment of the determination of personal status and legal status of any event of population and important events experienced by residents residing within or outside the territory of the Unitary State of the Republic of Indonesia. Respect for the diversity of a nation is a feature of the implementation of a democratic State. The realization of Indonesia as a democratic country is one of them carried out by laying the foundations for the implementation of human rightsin the constitution. With the inclusion of human rights in the constitution of the 1945 Constitution, every Indonesian citizen has the same rights and position before the law and the government. To create a great nation in carrying out the wheels of development human resources are needed. To produce a reliable nation cadre and reliable human resources, every citizen must get a good educationhas legal status that is legal and recognized by the state. As we all know that every child who is going to school, the child's legal status will be asked by the school if they want to enroll in school, for example whether they have a Birth Certificate or not. If onlythe best sons and daughters of the Indonesian people who are supposed to be the directors of the nation's generation in the future many cannot get education / school because they do not have birth certificates, which is unfortunate.Since South 2012, Kabupaten Tapanuli has implemented Law Number 23 of 2006 concerning Population Administration, especially article 32 paragraph 2,where every child aged 1 (one) year is more when managing his birth certificate through the process of the District Court. This study aims to assess the effectiveness or ineffectivenessLaw Number 23 of 2006 concerning Population Administration in South Tapanuli Regency and how the level of community participation in South Tapanuli Regency has been sinceLaw Number 23 Year 2006 is implemented.Finally it can be concluded that, with the implementation of Law Number 23 of 2006 concerning Population Administration in South Tapanuli District, it is very ineffectiveand the level of community participation is very low. To anticipate Law Number 23 of 2006, especially article 32 paragraph 2, the Government of South Tapanuli Regency carried out a collaboration with the State Court in the meeting to implement a circuit court inDistrict in South Tapanuli Regency